Enhanced sequestration of molybdenum(VI) using composite constructed wetlands and responses of microbial communities. (2nd February 2022) - Chen, B.; Zhou, F. J.; Yang, F.; Lian, J. J.; Ye, T. R.; Wu, H. Y.; Wang, L. M.; Song, N.; Liu, Y. Y.; Hui, A. Y.
Abstract: The molybdenum (Mo) non-point source pollution in the mining area has an irreversible impact on the surrounding water and soil ecosystems. Herein, three integrated vertical subsurface flow constructed wetlands (CWs) were constructed to assess the effects of combination substrates and plant on the removal of Mo(VI). Results showed that CW1 with combination substrates and cattail exhibited a favorable removal performance for Mo(VI) at 80.90%. Moreover, most Mo(VI) retained in the CWs was retained in the substrate (58.13–88.04%), and the largest fraction of Mo(VI) retained was the water-soluble fraction on the surface of the combination substrates. Mo(VI) removal was also influenced by the microbial community composition in substrate, especially their co-occurrence networks. The species that showed significant positive correlation with Mo(VI) removal were Planctomycetes, Latescibacteria, Armatimonadetes, and Gemmatimonadetes. Moreover, CWs added plants showed that more co-occurrences interaction between taxa occurs, which means that the wetlands efficiently select recruitment of potential microbial consortia and change the co-occurrences to remove pollution in the substrate. These results could be useful in providing an ecology-based solution for the treatment of Mo(VI) in wastewater, especially in adjusting the microbial communities for Mo(VI) removal at the genetic level. HIGHLIGHTS: Complex substrates coupled cattail enhanced Mo(VI) removal in constructed wetlands. Adsorption was the main Mo(VI) removal mechanism by DWTRs and MCPP. Mo(VI) removal was also influenced by microbial community composition. Cattails changed the co-occurrences of microbes to remove pollution in substrates. Graphical Abstract